2018
DOI: 10.1101/256404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Durability of environment-recruitment relationships in aquatic ecosystems: insights from long-term monitoring in a highly modified estuary and implications for management

Abstract: The environment can strongly influence the survival of aquatic organisms and their resulting dynamics. Our understanding of these relationships, typically based on correlations, underpins many contemporary resource management decisions and conservation actions. However, such relationships can break down over time as ecosystems evolve. Even when durable, they may not be very useful for management if they exhibit high variability, context dependency, or non-stationarity. Here, we systematically review the litera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Increased frequency of drought in the future may lead to further decline or extinction of SFE‐endemic pelagic fish species such as delta smelt and longfin smelt (Hobbs et al 2017) and the proliferation of drought‐tolerant nonnative fish species commonly found in littoral habitat (Davis et al 2019). It is increasingly important for water management operations to optimize water release timing and location such that they balance human and environmental needs (Chen and Olden 2017), and to do so under an adaptive management framework (Tamburello et al 2019). Successful environmental flow management for species of concern would also require the proper consideration of other conservation measures such as habitat restoration, invasive species management, reduced contaminant loading, and climate change mitigation (Arthington et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased frequency of drought in the future may lead to further decline or extinction of SFE‐endemic pelagic fish species such as delta smelt and longfin smelt (Hobbs et al 2017) and the proliferation of drought‐tolerant nonnative fish species commonly found in littoral habitat (Davis et al 2019). It is increasingly important for water management operations to optimize water release timing and location such that they balance human and environmental needs (Chen and Olden 2017), and to do so under an adaptive management framework (Tamburello et al 2019). Successful environmental flow management for species of concern would also require the proper consideration of other conservation measures such as habitat restoration, invasive species management, reduced contaminant loading, and climate change mitigation (Arthington et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Increased frequency of drought in the future may lead to further decline or extinction of SFE-endemic pelagic fish species such as Delta Smelt and Longfin Smelt (Hobbs et al 2017) and the proliferation of drought tolerant non-native fish species commonly found in littoral habitat (Davis et al 2019). It is increasingly important for water management operations to optimize water release timing and location such that they balance human and environmental needs (Chen and Olden 2017), and to do so under an adaptive management framework (Tamburello et al 2019).…”
Section: Management Implicationsmentioning
confidence: 99%
“…However, California's water resources are scarce and an evergrowing competing demand for water lies in the future. It is increasingly important for water management operations to optimize water release timing and location such that they balance human and environmental needs (Chen and Olden 2017), and to do so under an adaptive management framework (Tamburello et al 2019…”
Section: Management Implicationsmentioning
confidence: 99%
“…In fact, in his review of the fisheries literature, Myers (1998) found that few correlations between environmental conditions and fish recruitment held when they were re‐examined using new data. Despite this finding, environment–recruitment correlations are often used to inform the management of fish populations (Planque & Buffaz, 2008; Tamburello et al., 2019). Therefore, the use of analytical techniques capable of detecting changes in the importance of environmental conditions to fish recruitment is critical to better informing resource management.…”
Section: Introductionmentioning
confidence: 99%